Psychological Factors Influencing on the Motivation to Study of Students of TEI - Aprielieva, Iryna V. (2021)
The importance of psychological factors is manifested in the ability of students to acquire knowledge, gaining skills, perception of educational information, attitude to others, mutual understanding with people around. Taking this into consideration, the purpose of the academic paper is to study the basic aspects of the development of teachers’ professional competence in the context of transformational processes in education. Such methods as: theoretical analysis, description, comparison, synthesis, grouping, measurement, observation and experiment, have been used in order to achieve the purpose and objectives outlined in the academic paper. It has been established that the motivation of students to carry out educational and professional activities is a set of psychological factors, through the influence of which the interconnection between the motivation and desire of the student to study is conducted. In the course of the investigation, it has been found that the influence of psychological factors is quite effective in the case of motivating students to study. It has been proven that increasing the motivation of students to study is possible through: a common learning environment in the students’ collective; students’ participation in discussions, conferences, competitions; work in groups; application of innovative technological methods of studying educational material.